Cement Augmentation in Sacroiliac Screw Fixation Offers Modest Biomechanical Advantages in a Cadaver Model. Issue 11 (November 2016) - Osterhoff, Georg; Dodd, Andrew E.; Unno, Florence; Wong, Angus; Amiri, Shahram; Lefaivre, Kelly A.; Guy, Pierre
Abstract: Background: Sacroiliac screw fixation in elderly patients with pelvic fractures is prone to failure owing to impaired bone quality. Cement augmentation has been proposed as a possible solution, because in other anatomic areas this has been shown to reduce screw loosening. However, to our knowledge, this has not been evaluated for sacroiliac screws. Questions/purposes: We investigated the potential biomechanical benefit of cement augmentation of sacroiliac screw fixation in a cadaver model of osteoporotic bone, specifically with respect to screw loosening, construct survival, and fracture‐site motion. Methods: Standardized complete sacral ala fractures with intact posterior ligaments in combination with ipsilateral upper and lower pubic rami fractures were created in osteoporotic cadaver pelves and stabilized by three fixation techniques: sacroiliac (n = 5) with sacroiliac screws in S1 and S2, cemented (n = 5) with addition of cement augmentation, and transsacral (n = 5) with a single transsacral screw in S1. A cyclic loading protocol was applied with torque (1.5 Nm) and increasing axial force (250‐750 N). Screw loosening, construct survival, and sacral fracture‐site motion were measured by optoelectric motion tracking. A sample‐size calculation revealed five samples per group to be required to achieve a power of 0.80 to detect 50% reduction in screw loosening. Results: Screw motion in relation to the sacrum during loading with 250 N/1.5 Nm was not different among the three groups (sacroiliac: 1.2 mm, range, 0.6‐1.9; cemented: 0.7 mm, range, 0.5‐1.3; transsacral: 1.1 mm, range, 0.6‐2.3) (p = 0.940). Screw subsidence was less in the cemented group (3.0 mm, range, 1.2‐3.7) compared with the sacroiliac (5.7 mm, range, 4.7‐10.4) or transsacral group (5.6 mm, range, 3.8‐10.5) (p = 0.031). There was no difference with the numbers available in the median number of cycles needed until failure; this was 2921 cycles (range, 2586‐5450) in the cemented group, 2570 cycles (range, 2500‐5107) for the sacroiliac specimens, and 2578 cycles (range, 2540‐2623) in the transsacral group (p = 0.153). The cemented group absorbed more energy before failure (8.2 × 10 5 N*cycles; range, 6.6 × 10 5 ‐22.6 × 10 5 ) compared with the transsacral group (6.5 × 10 5 N*cycles; range, 6.4 × 10 5 ‐6.7 × 10 5 ) (p = 0.016). There was no difference with the numbers available in terms of fracture site motion (sacroiliac: 2.9 mm, range, 0.7‐5.4; cemented: 1.2 mm, range, 0.6‐1.9; transsacral: 2.1 mm, range, 1.2‐4.8). Probability values for all between‐group comparisons were greater than 0.05. Conclusions: The addition of cement to standard sacroiliac screw fixation seemed to change the mode and dynamics of failure in this cadaveric mechanical model. Although no advantages to cement were observed in terms of screw motion or cycles to failure among the different constructs, a cemented, two‐screw sacroiliac screw construct resulted in less screw subsidence and greater energy absorbed to failure than an uncemented single transsacral screw. Clinical Relevance: In osteoporotic bone, the addition of cement to sacroiliac screw fixation might improve screw anchorage. However, larger mechanical studies using these findings as pilot data should be performed before applying these preliminary findings clinically.